Icke-linjära beräkningar av fångmun hos lastbilskoppling - Gren, Daniel; Johansson, Niklas (My University, 2017)
This Bachelor’s thesis has been done in cooperation with the client who offered the thesis, in order to propose a new solution for a guiding funnel to a truck coupling. The assignment was introduced with the issue of having difficulties when connecting the truck to the trailer on hilly terrain. The work consists mainly of CAD-modeling in Autodesk Inventor 2017 and nonlinear calculations with FEA in Ansys 17.1. The CAD-modeling was used for designing new guiding funnels and the calculations were done to verify that the new guiding funnels met the requirements that the client suggested. The project was limited by only designing the guiding funnels to withstand a single situation of a static load. The calculations assumed that the materials were isotropic and was following a multilinear stress curve in order to define the material as ideal plastic. Three guiding funnels were made whereas only two were valid according to the the requirements. The reliability of the results are discussed and improvements are suggested by potential errors that might have been evident in the calculations. The final decisions are discussed but the responsibility of choosing was given back to the client.
Keywords: Teknisk mekanik; Applied Mechanics